REPRESENTATION OF KNOWLEDGE MOTHER ABOUT CONSUMPTION NUTRIENTS WORTH TODDLERS IN VILLAGE NAME SAWIT DISTRICTS OF BOYOLALI - STIKES DUTAGAMA KLATEN (STIKES DUTAGAMA KLATEN, 2014)
Background: Age baby and toddler so prone to problems because the nutrients in infant and toddler time is important dalam future growth. Issues related nutrients with snack filter and baby toddler consumption. Particularly infants and toddlers in consumption snack aspects have to chime with consumption. Children under five consumption snack Many people come depending dark or caregiver. So, Get dikatakan flowers that grow children 1-5 years old depending in how much people old baby and toddler snack consumption adjust worth their nutrients. Objective: Research for this bertujuan mengetahui representation of knowledge mother about consumption nutrients worth toddlers in the name of village, district Sawit, Boyolali district. Methods: Type of design and research using descriptive methods. Population dalam research all these are the closest mother has a child under five in the name of the village district of Sawit Boyolali. Engineering recruitment with purposive sample Sampling, with the number of 51 respondents. Tools aggregation of data filter used are the proprietary questionnaire. Process the data using a computer, with one dianalisis univariat. Results: respondent filter criteria has good knowledge sebesar of 66.60% or 34 respondents, criteria have enough knowledge sebesar seabanyak 27.50% or 14 respondents, less scientific criteria sebesar or 5.90% of respondent 3. Conclusion: Description of knowledge mother about consumption nutrients worth toddlers in the name of the village district of Boyolali Sawit including dalam criteria of good news is 66.60% (34) respondents from 51 respondents.